BRAF and TERT promoter mutations in the aggressiveness of papillary thyroid carcinoma: a study of 653 patients - Jin, Langping (Oncotarget, 2016)
The role of telomerase reverse transcriptase (TERT) gene promoter mutations in the aggressiveness of papillary thyroid cancer (PTC) remains to be further investigated. Here we examined the relationship of TERT promoter mutations and BRAF V600E with the clinicopathological features of PTC in 653 patients. Sanger sequencing of genomic DNA from primary PTC tumors was performed for mutation detection and genotype-clinicopathological correlation of the tumor was analyzed. BRAF V600E and TERT promoter mutations were found in 63.7% (416 of 653) and 4.1% (27 of 653) of patients, respectively; the latter became 9.8% when only tumors ≥ 1.5 cm were analyzed. TERT promoter mutations occurred more frequently in BRAF mutation-positive cases compared to wild-type cases, being 5.3% in the former versus 2.1% in the latter (P = 0.050). BRAF and TERT promoter mutations were each significantly associated with high-risk clinicopathological features of PTC, such as old patient age, large tumor size, extrathyroidal invasion, capsular invasion, and advanced disease stages. Coexistence of BRAF V600E and TERT promoter mutations was particularly associated with high-risk clinicopathological features, as exemplified by extrathyroidal invasion seen in 54.5% (12/22) of patients harboring both mutations versus 9.9% (23/232) of patients harboring neither mutation (P < 0.001). Thus, this study, the largest on TERT mutation so far, demonstrates a significant role of BRAF V600E and TERT promoter mutations in the aggressiveness of PTC, which is particularly robust and cooperative when the two mutations coexist. These results, together with previous studies, establish a significant role of these mutations in the aggressiveness of PTC.